Effectiveness of Farming Cards in the Distribution of Subsidized Fertilizers in Sijunjung District - Vivi Hendrita; Fadilla Meidita; Juli Supriyanti (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Distribution of subsidized fertilizer from the government benefits farmers because they can buy fertilizer at affordable prices and good quality. In practice, the distribution of subsidized fertilizer often experiences various obstacles. The main problems with the performance of subsidized fertilizer distribution are planning, distribution, and supervision. This research aims to determine the effectiveness of using farmer cards in distributing subsidized fertilizer in Sijunjung Regency. The type of research used is descriptive research with survey methods. The study sample was selected as 100 people using the Taro Yamame sampling method. The sample of farmers was selected purposively: farmers who had received a farmer's card. Primary data was collected using a questionnaire prepared using the Guttman scale. Data analysis was descriptively qualitatively and triangulated to validate the data and reduce bias. The research results show that the effectiveness of using farmer cards to distribute subsidized fertilizer is considered less than optimal. Due to various obstacles in the field, many farmers still have difficulty using farmer cards to redeem subsidized fertilizer. The long distance to the bank and farmers' lack of understanding regarding the procedures for using the farmer's card in banking are the main reasons for not achieving the aim of the farmer's card in distributing subsidized fertilizer in Sijunjung Regency. In terms of the effectiveness of fertilizer distribution based on the 6T indicators (right price, type, time, place, quantity, and quality), distribution is considered quite effective. However, price effectiveness is still less than optimal because the price of fertilizer purchased by farmers often exceeds the HET (Highest Retail Price) set by the government. According to the HET, this requires further monitoring to ensure that subsidized fertilizer prices remain affordable.